Strife and progress : portfolio strategies for managing urban schools - Hill, Paul T. (Paul Thomas), 1943- (Brookings Institution Press, 2013)
Deficient urban schooling remains one of America's most pressing-and stubborn-public policy problems. This important new book details and evaluates a radical and promising new approach to K-12 education reform. Strife and Progress explains for a broad audience the ""portfolio strategy"" for providing urban education-its rationale, implementation, and results. Under the portfolio strategy, cities use anything that works, indifferent to whether schools are run by the public district or private entities. It combines traditional modes of schooling with newer methods, including charterin